2015
DOI: 10.1039/c5ta01778e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermoelectric performance of β-Zn4Sb3 through resonant distortion of electronic density of states doped with Gd

Abstract: The thermoelectric properties of Gd-doped β-Zn4Sb3 are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Thus, efforts have been made to include elements ubstituting/dopingi nto the Zn site including Cd doping, [39] Mg doping, [29] Bi doping, [40] Gd doping, [41] or thermalp rocessing in inert gas (e.g. Thus, efforts have been made to include elements ubstituting/dopingi nto the Zn site including Cd doping, [39] Mg doping, [29] Bi doping, [40] Gd doping, [41] or thermalp rocessing in inert gas (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, efforts have been made to include elements ubstituting/dopingi nto the Zn site including Cd doping, [39] Mg doping, [29] Bi doping, [40] Gd doping, [41] or thermalp rocessing in inert gas (e.g. Thus, efforts have been made to include elements ubstituting/dopingi nto the Zn site including Cd doping, [39] Mg doping, [29] Bi doping, [40] Gd doping, [41] or thermalp rocessing in inert gas (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, improving the thermals tability of Zn 4 Sb 3 materials could have benefits for practical applications. Thus, efforts have been made to include elements ubstituting/dopingi nto the Zn site including Cd doping, [39] Mg doping, [29] Bi doping, [40] Gd doping, [41] or thermalp rocessing in inert gas (e.g. Ar), [34] or melt-spun preparation, [42] or compositingZ n 4 Sb 3 with nanostructures, [17] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Simonson et al 136 have shown the inclusion of V in Hf 0.75 Zr 0.25 NiSn HH leads to a rise in DOS at the Fermi level governing the resonant state and enhanced thermopower. This phenomenon is observed in β -Zn 4 Sb 3 by doping of Sm, 137 Pr, 138 and Gd, 139 and consequently improved thermopower was obtained due to a sharp rise in the density of states near the Fermi level.…”
Section: Achieving Resonant State To Increase Seebeck Coefficientmentioning
confidence: 85%
“…As can be seen in Figure 4(d), Ag 0.02 Zn 4 Sb 3 reported in reference [39] shows relatively poor thermoelectric performance. For the other state-of-art doped Zn 4 Sb 3 samples reported before, most dopants chosen are either toxic (Cd [9], Pb [24]) or expensive rare-earth elements (Pr [40], Sm [41], Gd [42]) to enhance the thermopower through resonant distortion of electronic density of states (DOS). Due to Ge [43] and Nb [13] dopants are sensitive to oxygen the experimental operation should be done in the glove box.…”
Section: Thermoelectric Performancementioning
confidence: 99%
“…Moreover, these doped Zn 4 Sb 3 samples reported do not show better thermoelectric performance than the Ag-doped sample (Zn 0.9925 Ag 0.0075 ) 4 Sb 3 in our work. The thermoelectric figure of merit zT for the best-performing Ag-doped sample (Zn 0.9925 Ag 0.0075 ) 4 Sb 3 is obviously higher than other state-of-art doped Zn 4 Sb 3 materials in the temperature range of 375 -575 K. [1,9,13,23,24,[39][40][41][42][43] are plotted for comparison.…”
Section: Thermoelectric Performancementioning
confidence: 99%